2014
DOI: 10.1186/1471-2407-14-419
|View full text |Cite
|
Sign up to set email alerts
|

Increased health care utilization by survivors of childhood lymphoblastic leukemia is confined to those treated with cranial or total body irradiation: a case cohort study

Abstract: BackgroundPrevious studies have indicated that survivors of childhood acute lymphoblastic leukemia (ALL) have an increased morbidity measured in terms of health care utilization. However, earlier studies have several potentially important limitations. To overcome some of these, we investigated hospital contact rates, and predictors thereof, among 5-year survivors of ALL in a population-based setting, and compared them to a control cohort regarding outcome measures from a comprehensive nation-wide health regist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Tobacco is recognized as the major preventable risk factor for most cancers [ 103 ], contributing to one in three cancers [ 104 ]. Tobacco has been associated with lung, oral cavity, pharynx, larynx, esophagus, stomach, liver, urinary tract, cervix, and other cancers [ 105 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco is recognized as the major preventable risk factor for most cancers [ 103 ], contributing to one in three cancers [ 104 ]. Tobacco has been associated with lung, oral cavity, pharynx, larynx, esophagus, stomach, liver, urinary tract, cervix, and other cancers [ 105 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study, which uses linked rather than self-reported data and population controls, is one of only two (17) to separate secondary care activity associated with cancer follow-up from activity associated with other morbidities; finding that survivors not only experienced higher rates of admission but also higher rates of outpatient visits, neither of which abated over their TYA years. Reported less often are the types of conditions underlying these associations, with four studies assessing risks by organ system (8,12,14,17). Survivors in these studies were diagnosed over a wider period than the study reported here, and had median follow-up times that were shorter; 9 to 17 years from diagnosis, compared to 25 years here.…”
Section: Discussionmentioning
confidence: 99%
“…(4)(5)(6) With respect to the latter, however, much of the information on late effects among survivors has come either from analyses of hospitalizations or from questionnaires completed by consenting individuals. (7)(8)(9)(10)(11)(12)(13)(14)(15)(16) As is evident from the studies summarized in Table 1 (which includes those that examined all leukaemias combined and those that also included young adults), less attention has been paid to chronic conditions that do not require hospital admission, (17,18) and to morbidity patterns that change over time. (11,19) The longitudinal data examined in this report contain information on hospital outpatient attendances, as well as inpatient episodes, cancer registrations, and deaths.…”
Section: Introductionmentioning
confidence: 99%
“…Follow-up care of the growing population of childhood cancer survivors will become a public health concern [2,3,5,7]. It is therefore important to provide high-quality and cost-effective care for this population with increased medical needs [38][39][40][41]. A model of care including not only specialists but also primary care physicians might prevent over-or undertreatment of survivors and thereby reduce loss to follow up [42][43][44].…”
Section: Discussionmentioning
confidence: 99%